Interprofessional Teamwork to Promote Health: First-Time Parents' Experiences of a Combined Home Visit by Midwife and Child Health Care Nurse - Sjögren Forss, Katarina; Mangrio, Elisabeth; Hellström, Lisa (Frontiers in Pediatrics, 2022)
Background To achieve the requisites for a child’s healthy development and to reduce health inequalities, it is important to promote health initiatives at an early stage in a child’s life and to include the parents. Home visits by healthcare professionals have been found to have positive health effects for both the baby and the parents. From an extended home visit programme in Sweden, our aim was to illuminate first-time parents’ experience of a home visit conducted by a midwife and a child health care nurse 1–2 weeks postnatal. Methods Data was collected by interviews (n = 13) with first-time parents. The transcribed texts were analysed using inductive content analysis. Results The participants’ experiences could be understood from the two themes, Feeling safe and Feeling secure, and the content within these themes was unified in one overarching theme, A sense of trust. The participants experienced that the midwives and the child health care nurses complemented each other, and there was a perception of respect towards each other’s field of knowledge. Conclusions By meeting both professionals at the same time and in their own home, the participants experienced that the needs of the baby and their needs and concerns as new parents were included and supported. This made them feel secure and safe.